Contribution of phenotypic characters in deciding the price of different categories of buffaloes - Dixit, Vishwa Bharati (Indian Journal of Dairy Science, 2017)
The study was conducted in Haryana and 240 farmers of 8 villages of 4 districts constituted the study sample. Response of 100 traders was also elicited to identify four villages from where maximum sale of buffaloes took place (category-I). Similarly, four villages were identified from where comparatively less sale of buffaloes took place (category-II). The sample included 120 respondents each from the two categories of villages (category-I and category-II). Cumulatively responses of two categories indicated that milk yield (4.90), parity (4.24), shape and size of udder (4.23) were most important phenotypic parameters which significantly contributed to the price of different categories of buffaloes. Phenotypic characters enabled farmers to predict their price to the extent of 95 percent in case of lactating while these were helpful to the extent of 87 and 42 percent in case of dry/pregnant buffaloes and heifers respectively.